STUDENTS' RECEPTION OF COVID-19 NEWS ON CNN INDONESIA "GOOD MORNING" PROGRAM - Rachma, Siti; Kholisoh, Nur (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2020)
The news of the coronavirus or Covid-19 has become a hot topic of discussion in the last few months. This article investigates the student's reception of the Corona Virus Alert segment broadcasted through the CNN Indonesia news program, "Good Morning." Using Stuart Hall's reception studies model, we conducted in-depth interviews with five students who watched Covid-19 news intensively on "Good Morning," CNN Indonesia. We found that students decode differently the meaning of messages conveyed by the information. Some coded the story in a hegemonic or dominant position --it means they agree with what and how the media frame the events and phenomena. On the other hand, some interpreted the meaning conveyed through the news with a different perspective, indicating they are in the oppositional position. They criticized the media for providing inaccurate, even factual, information. This study is vital in the midst of the Covid-19 pandemic information storm conveyed by both the media and the public. It becomes a reference for how the audience can interpret news differently and can share their interpretations with the community according to what they receive. To cite this article (7th APA style):Rachma, S. & Kholisoh, N. (2020). Students' Reception of Covid-19 News on CNN Indonesia "Good Morning" Program. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(2), xx-xx. http://dx.doi.org/10.36782/jcs.v10i2.2104